Weight Management Challenges and Opportunities - Heshmati, Hassan M. (IntechOpen, 2022)
The physiological or pathological variations in the amount or mass of each component of body weight can lead to an increase or a decrease in total body weight, with a potential risk of increased morbidity and mortality. This book presents an overview of current knowledge about different types of body weight changes, with a special emphasis on obesity.